Former les enseignants par et/ou à l’improvisation ? - Guillaume Azéma; Serge Leblanc (Activités)
This article provides an overview of research which, at the international level, has addressed or is addressing the issues training teachers through and/or in improvisation. After proposing elements of problematization which bring the subject matter into tension, a six-axis summary highlights a series of opposing training biases that might fuel dialectic games. To understand these possible games, we developed two illustrations. We then present a summary of training methods or of ways to support the development of professionalism through and/or towards improvisation. The article as a whole leads to a discussion and a conclusion which defend: (a) the value of not confusing training through and/or in improvisation, with training through and/or in adaptation, and (b) the fact that training through and/or in improvisation will remain “entre chien et loup” (an “in‑between”).